2018
DOI: 10.5539/jel.v7n3p109
|View full text |Cite
|
Sign up to set email alerts
|

Teaching of Basic Posture Skills in Visually Impaired Individuals and Its Implementation Under Aggravated Conditions

Abstract: The aim of this study is to enable basic posture exercises to be included in the basic exercises of the visually impaired individuals as a step to learn more difficult movements, to guide the instructors in order to make efficient progress in a short time and to help more numbers of disabled individuals benefit from these studies.Method: 15 visually impaired sedentary students from the Department of Special Education, the Gazi Faculty of Education, who take the course Physical Education and Game Teaching for V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…Examination of the study results revealed an improvement in the walking quality in visually impaired individuals, an increase in the ability to maintain balance at walking speed, and a decrease in loss of balance. When the measurement methods, exercise protocols, and results of the studies are evaluated, they are found to be similar to the results of previous research ( Suveren-Erdogan et al, 2018 ; Suveren-Erdogan and Suveren, 2018 ). Another study highlighted the importance of teaching basic postures, body awareness, and spatial orientation in teaching movement and sports skills to visually impaired individuals ( Suveren-Erdogan et al, 2018 ).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Examination of the study results revealed an improvement in the walking quality in visually impaired individuals, an increase in the ability to maintain balance at walking speed, and a decrease in loss of balance. When the measurement methods, exercise protocols, and results of the studies are evaluated, they are found to be similar to the results of previous research ( Suveren-Erdogan et al, 2018 ; Suveren-Erdogan and Suveren, 2018 ). Another study highlighted the importance of teaching basic postures, body awareness, and spatial orientation in teaching movement and sports skills to visually impaired individuals ( Suveren-Erdogan et al, 2018 ).…”
Section: Discussionsupporting
confidence: 79%
“…After being verbally informed of the study to be conducted, visually impaired participants were asked to walk from heel to toe on a 10-meter line, with the heel of the foot touching the toe of the foot on the ground at each step, accompanied by an audio stimulus to detect spatial orientations and loss of balance. Total walking error values were recorded at the end of the test ( Bruininks, 1978 ; Suveren-Erdogan and Suveren, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Suveren-Erdoğan and Suveren (2018) concluded that basic position exercises were highly effective in the development of such characteristics as the perception of obstructions, spatial orientation, postural control, and strength. Seemungal, Glasauer, Gresty, and Bronstein (2007) suggested that long-term training for blind people could affect navigation and orientation (a function of the vestibular system).…”
Section: Discussionmentioning
confidence: 99%
“…Sport training is of grave importance for visually impaired individuals (Suveren-Erdoğan & Suveren, 2018). In visually impaired individuals, the ability to act independently begins to develop with delay (Sarimski, 1990) and balance loss along with different postures and walking styles such as extending hands forward, walking with slow steps to avoid accidents and to move safely can be observed in these individuals (Arslantekin, 2014;Tuncer et al, 1999).…”
Section: Introductionmentioning
confidence: 99%